Evaluasi Implementasi Kebijakan Perpres Nomor 16 Tahun 2018 dalam Pengisian Jabatan Fungsional Sekda Kabupaten Mojokerto - Kadek Saptanita; Dyah Sawitri; Dwi Orbaningsih; Tri Cicik Wiyanti; I Made Murjana (Valid: Jurnal Ilmiah, 2023)
Implementation of government procurement of goods/services requires competent human resources. The aims of this research are to describe and analyze the evaluation, effectiveness, driving and inhibiting factors of Policy Implementation of Presidential Regulation Number 16 of 2018 in Filling Functional Positions During the Covid-19 Pandemic. The scope of this research is to evaluate the filling of functional positions for the manager of the procurement of goods and services in the Procurement Section of the Regional Secretariat of Mojokerto Regency for the 2020 period. This research uses a descriptive method with a qualitative approach. Data collection techniques using interviews. The results of the study showed that the implementation of the filling of functional positions for the manager of the procurement of goods and services in the Procurement Section of the Regional Secretariat of Mojokerto Regency has been running although it has not yet reached the target due to several factors.